2019
DOI: 10.3389/frobt.2019.00120
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of User-Applied Isometric Force/Torque Using Upper Extremity Force Myography

Abstract: Hand force estimation is critical for applications that involve physical human-machine interactions for force monitoring and machine control. Force Myography (FMG) is a potential technique to be used for estimating hand force/torque. The FMG signals reflect the volumetric changes in the arm muscles due to muscle contraction or expansion. This paper investigates the feasibility of employing force-sensing resistors (FSRs) worn on the arm to measure the FMG signals for isometric force/torque estimation. Nine part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Sakr et al used FSR 402 to estimate hand force using 16 channels at a 10 Hz sampling frequency. Finally, they obtained the R 2 accuracies of 0.83 for the 3-DoF force, 0.84 for 3-DoF torque, and 0.77 for the combination of force and torque (6-DoF) in cross-trial evaluation [ 42 ]. Except for the most widely used FSR sensor, the sampling frequency of other sensors is different, but most of them choose a lower sampling frequency to match the human body movement.…”
Section: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakr et al used FSR 402 to estimate hand force using 16 channels at a 10 Hz sampling frequency. Finally, they obtained the R 2 accuracies of 0.83 for the 3-DoF force, 0.84 for 3-DoF torque, and 0.77 for the combination of force and torque (6-DoF) in cross-trial evaluation [ 42 ]. Except for the most widely used FSR sensor, the sampling frequency of other sensors is different, but most of them choose a lower sampling frequency to match the human body movement.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Because FMG has the characteristics of intuitively reflecting muscle activity, it can reflect the magnitude of force by detecting the intensity of muscle activity to a certain extent. Sakr et al use a total of 60 FSRs embedded in four bands, estimating in two cases: (1) 3-DoF force and 3-DoF torque at once and (2) 6-DoF force and torque [ 42 ]. The results showed that FMG achieves a good performance in multiple-DoF force/torque estimation.…”
Section: Applicationmentioning
confidence: 99%
“…Several studies show the potential of FMG as an alternative control strategy for HMI applications, particularly for upper-limb prosthetic control [9]. In this context, Sakr et al demonstrated the feasibility of estimating hand isometric force/torque from FMG signals recorded via 60 FSRs, which were embedded into four bands and placed in different locations around the arm [149]. Again, Sakr et al showed the possibility of predicting force in dynamic conditions by using FSRs worn around the arm [150].…”
Section: Muscle Gross Motion-based Hmismentioning
confidence: 99%
“…Estimating isometric hand force from wrist, forearm, and upper arm FMG signals were found promising in [13]. Although a loadcell or a force/torque (FT) sensor can read forces precisely, it is bulky, requires complex signal processing units and is difficult to move freely when used as wearable on a human body.…”
Section: Introductionmentioning
confidence: 99%